ANALYSIS OF THE SUPPLY CHAIN OF CAYENNE PEPPER IN SOUTH SULAWESI - Sri Hardianti Rosadi; Fitry Purnamasari; Hasnah Hasnah (Agribusiness Journal, 2021)
This study aims analyzing supplay chain maps and activities in the cayenne pepper inSouth Sulawesi. This research was conducted in Enrekang Regency with the number ofrespondents as many as 5 farmers and traders. This study uses the is qualitativeresearch with naturalistic research methods which are natural research. The resultsshowed that Supply chain mechanism for cayenne pepper in South Sulawesi, startingfrom the flow of products from farmers, village collectors, wholesalers, inter-islandtraders to retailers. The flow of information on the supply chain of cayenne pepper iswell integrated between actors in the supply chain, while the flow of money occurs inaccordance with the agreement of actors in the supply chain. And Supply chain activitiesconsist of two actors in the supply chain, namely the main and supporting actors. Themain actors consist of farmers, village collectors, wholesalers, inter-city traders andretailers. Meanwhile, the supporting actors consist of agricultural extension agents,farmer groups, the Agriculture Service, Agribusiness Sub-Terminal, farmer shops, farmlaborers, inter-island traders, and consumers.